The Efficiency of Moringa oleifera seed biomass in the Removal of lead (II) ion in aqueous solution : Adsorption capacity of Moringa oleifera in the removal of Pb(II) ion from polluted water - Nwagbara, Victor Uzoma (European Journal of Applied Sciences, 2022)
This study was based on the evaluation of the efficiency and applicability of Moringa oleifera seed biomass (MOSB) as adsorbent in the removal of Lead (Pb) in water. The study was justified by the toxic nature of the study metal as the current conventional processes of heavy metals’ removal are not environmentally friendly and chemical coagulant very exorbitant. Fourier transform Infrared (FTIR) analysis was used to characterise the Moringa oleifera seeds biomass functional groups that may be present in the adsorption of metal ions. The observed components were the carboxylic acid and amine functional groups (-COOH and -NH). The effects of contact time, adsorbent dosage, metal ion concentration and pH were studied. Pb (II) ion had a maximum adsorption capacity of 90% at pH 5, room temperature, and 0.8 g dose of Moringa oleifera seeds biomass. The adsorption data fit better with the Langmuir than Freundlich isotherm models. From the Langmuir model, the sorption capacity (qm) of MOSB for Pb (II) ion was 6.19 mg/g. The results showed that Moringa oleifera seed biomass is an effective adsorbent in the removal of the studied heavy metal in water.